Promoting wastewater treatment in India: Critical questions of economic viability. (10th June 2022) - Bassi, Nitin; Kumar, Saurabh; Kumar, M. Dinesh; Van Ermen, Sofie; Campling, Paul
Abstract: The article shows that while there is rich literature on the cost‐effectiveness of wastewater treatment systems, little analysis exists on their economic viability that goes beyond direct benefits and costs to include externalities, which is very crucial for developing countries like India. This article first presents the results of life cycle cost assessment of various wastewater treatment technologies used in India. The article then shows that the direct benefits from treated wastewater are unlikely to be high in most situations due to lack of orientation towards the demand. It argues that for sustainable investments in wastewater treatment, the indirect benefits including public health benefits due to protection of drinking water sources, environmental benefits due to maintenance of aquatic life and improvement of soil health, which are determined by the socio‐economic and ecological conditions that vary across regions, should also be considered and quantified.